SEKOLAH UNTUK HIDUP: FUNGSI PENDIDIKAN SEBAGAI BEKAL BERTAHAN DI ZAMAN MODERN - Anis Fadhilah; Karlalia Felisiana; Ma’isyatul Ihtiyadh; Aufa Nur Afifa; Wiranti Shofiroh; Abdul Khobir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The current formal education system faces a fundamental problem, namely a functional shift from a medium for developing life skills toward a narrow and standardized academic orientation. This condition results in students not being fully equipped with the competencies needed to navigate the complexity of modern life. This study aims to examine the ideal function of education, analyze the factors contributing to this orientational shift, and formulate a conceptual framework for restoring education to its fundamental role as a foundation for survival in the modern age. This study employs a qualitative approach through descriptive-analytical library research. Data were obtained from relevant scientific literature, including books, journal articles, and research findings related to the philosophy of education, educational transformation, and twenty-first century challenges. Analysis was conducted using content analysis and conceptual analysis techniques with source triangulation to ensure the validity of the findings. The results reveal four key findings. First, education ideally constitutes a holistic process that prepares individuals intellectually, morally, and practically. Second, the pressures of globalization and academic standardization have significantly displaced educational priorities, causing vital competencies such as critical thinking and mental resilience to be increasingly marginalized. Third, the challenges facing modern education are multidimensional, encompassing technological, sociocultural, and human resource dimensions. Fourth, educational reform requires comprehensive renewal in life competency-based curriculum, active and contextual learning methodology, and institutional reorientation placing the formation of the whole person as the highest goal. This study concludes that school for life is a collective commitment that must be concretely realized across all aspects of educational practice.